Exploring the family effect on innovative capacity and earnings management - Ya-Fang Wang; Yen-Fang Kuo (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2020)
Purpose: This study examines whether family businesses (FBs) differ from non-FBs with regard to innovative strategies, and whether their innovation is a reflection of earnings management behavior. Design/methodology/approach: This study extended research into the issue of FBs by investigating innovation capacity and earnings management. We adopted the electronics industry in Taiwan (between 2010 and 2015) as a research sample to determine (1) whether family effects influence innovation performance at the firm level; (2) whether the innovation performance of FBs is an indication of earnings management behavior; and (3) the effects of family involvement and CEO-duality in FBs. Finding: Our results show that FBs are less likely than non-FBs to devote resources to increasing innovation. However, managerial participation of family members and a uniform CEOduality leadership was shown to strengthen efficiency and flexibility in decision-making, thereby enhancing innovation capacity. We also found that FBs with higher innovation capacity are less likely to window-dress earnings. This association is more pronounced in cases of CEO-duality leadership, which implies that FBs' innovative ambitions and duality leadership had greatly advanced in operating performance and corporate governance, and thus restrain managerial self-interested behavior. Research limitations/implications: This study had a number of limitations. First is the measure of innovative capacity. There are a number of ways of measuring innovation, and we posit that patents are superior to R&D investment when investigating innovation capacity. Second, our results may have been affected by other determinants of innovation capacity, despite the fact that we adopted several control variables, such as financial characteristics, which may be correlated with innovation outcomes. Third, we used discretionary accruals as a proxy for earnings management; however, this does not necessarily reflect actual practices of earnings management. Although such proxies have been consistently used in previous research, may provide rich insights into earnings management behavior. Despite the noted limitations, our evidence clearly suggests the following: (1) FBs with strong family involvement in management and CEO-duality leadership tend to have higher innovation capacity; and (2) FBs with quality innovation capacity are less likely to engage in earnings management. Originality/value: This study fills a gap in the research on FBs by providing evidence concerning the effects of family on innovation and earnings management. Our findings have important implications for future research as well as the establishment of regulations and standards. Our findings provide evidence of a positive association between family effects and innovation capacity, which depends on the degree of family involvement in management and leadership structure. We found that family governance has a significantly positive impact on the competitive advantage of FBs. We also found that the innovation capacity of FBs is negatively associated with earnings management behavior. This study also re-examines the apparent contradictions in previous findings related to earnings management among FBs, while contributing to the literature linking family effects and governance mechanisms to earnings management behavior.
Keywords: M41; 330; family business; family involvement; CEO-duality; innovation; earnings management